The effect of gene polymorphism of certain cytokines on echocardiographic parameters in patients with chronic rheumatic heart disease - V. S. Petrov (Российский кардиологический журнал, 2019)
Aim. To assess the effect of polymorphism of tumor necrosis factor-а (TNF-α) cytokines and interleukin (IL-17A, IL-17F, IL-10) on echocardiographic parameters in patients with chronic rheumatic heart disease (RHD).Material and methods. A total of 128 patients with RHD were examined, average age was 58,96±0,34 years. Echocardiography was performed on a Philips Affinity 50 machine. Genotyping was carried out using polymorphic TNF-α markers (G308A, IL-10 G1082A, IL-17A G197A, IL-17F А161Н0 by polymerase chain reaction with an electrophoretic scheme for detecting the result of “SNP-EXPRESS”.Results. RHD homozygotes for TNF-а A308A had the largest linear dimensions of the left ventricle (left ventricle end-diastolic dimension (LVED) — 5,80±0,22 cm, left ventricle end-systolic dimension (LVES) — 3,93±0,27 cm), as well as the studied homozygous for IL-17A A197A (LVED — 5,81±0,13 cm, LVES — 3,78±0,11 cm). In group of TNF-α G308G homozygotes, values of right heart (right ventricle — 2,75±0,05 cm, right atrium — 4,80±0,11 cm) were the largest and mitral valve orifice area (MVOA) was smallest — 1,52±0,04 cm2. Heterozygous patients with IL-17F Д161Н also had a greater dilatation of the ventricles compared with homozygotes of IL-17F Н161Н, in which parameters were close to normal (LVED 5,58±0,05 cm, LVES 3,68±0,04 cm). There was no statistically significant difference in linear sizes of the left and right heart in patients with IL-10 polymorphism. IL-10 polymorphism patients had statistically significant MVOA differences: minimum MVOA in G1082A heterozygotes — 1,40±0,06 cm2 and maximum — 1,64±0,04 cm2 in G1082G homozygotes. IL-10 G1082G homozygotes was characterized by maximum values of interventricular septum — 1,13±0,04 cm, left ventricular posterior wall — 1,10±0,03 cm.Conclusion. Homozygosity of TNF-α A308A and IL-17A A197A in RHD patients leads to the largest linear sizes of the left ventricle, and homozygosity for TNF-а G308G — to the maximum sizes of the right heart and left atrium against the background of the minimum sizes of MVOA. IL-10 polymorphism has not effect on heart linear dimensions, but IL-10 G1082G leads to maximum MVOA size.